2005
DOI: 10.1111/j.1365-294x.2005.02613.x
|View full text |Cite
|
Sign up to set email alerts
|

Temporal variation of the population structure and genetic diversity of Farfantepenaeus notialis assessed by allozyme loci

Abstract: Population genetic studies carried out on penaeid shrimps have disclosed different patterns of population subdivision, revealing new aspects of shrimp biology as well as the effects of historical contingency molding those patterns. However, the stability of observed allele frequencies over time still remains untested. The objective of this article is to show the analysis of the temporal variation of allozymes in a shrimp species inhabiting Cuba which proves that the genetic structure of this species could sign… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(20 citation statements)
references
References 82 publications
0
19
0
Order By: Relevance
“…Most of the available research is limited in terms of its description and discussion of observed genetic patterns. These studies assume that observed patterns will remain stable over time, and that variable factors have little or no effect over relatively short time periods (Barcia et al 2005). However, some studies have documented the relevance of long-term genetic stability research, particularly in the context of understanding which factors have led to the establishment of observed patterns (Barcia et al 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Most of the available research is limited in terms of its description and discussion of observed genetic patterns. These studies assume that observed patterns will remain stable over time, and that variable factors have little or no effect over relatively short time periods (Barcia et al 2005). However, some studies have documented the relevance of long-term genetic stability research, particularly in the context of understanding which factors have led to the establishment of observed patterns (Barcia et al 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Significant population differentiation at a small geographic scale (20-50 km) as well as significant genetic isolation between the southern gulfs, separated by 350 km, was identified (Borrell et al 2004;Espinosa et al 2003;García-Machado et al 2001;Robainas et al 2005). Nevertheless, the only study on a Cuban reef fish species, Acanthurus tractus Poey, 1860, has shown no population differentiation in the archipelago using partial cytochrome b sequences (Castellanos-Gell et al 2012).…”
Section: Introductionmentioning
confidence: 90%
“…Larval transport by marine currents, extended pelagic larval phase and larval behavior are the most common reasons given for this wide connectivity. However, contradictory patterns may often appear in species with similar life history traits, suggesting that a fluctuating hydrodynamic regime (Robainas et al 2005;Severance and Karl 2006) and the highly stochastic nature of larval transportation through large distances (McCartney et al 2000) may also influence the genetic connectivity of marine populations.…”
Section: Introductionmentioning
confidence: 97%
“…Other studies have also concluded that extrinsic factors (i.e., unstable environmental conditions) might promote changes in the genetic structure of natural populations of some species (Garant et al 2000;Roark et al 2001;Østergaard et al 2003;Barcia et al 2005;Huang et al 2005;Cena et al 2006). Besides environmental factors, biological factors such as genetic drift and natural selection could also mold genetic patterns (Alam and Islam 2005;Barcia et al 2005;Crispo et al 2006;Mäkinen et al 2006;Gutiérrez-Rodríguez et al 2007;Lee and Boulding 2007;Rahman et al 2008). Genetic drift is most important in small populations, while natural selection is more effective in larger populations and could be enhanced by unstable environments (Frankham et al 2002).…”
Section: Maintenance Of Genetic Variationmentioning
confidence: 97%
“…Genetic structure of natural populations is not always stable over time, however. Recently, many scholars have paid more attention to the temporal changes in population genetic structure and discussed the cause of this variation (Østergaard et al 2003; Barcia et al 2005;Florin and Höglund 2007;Lee and Boulding 2007;Martínez-Cruz et al 2007). Significant temporal variation was detected in small populations of gastropods, shrimp, and fish.…”
Section: Introductionmentioning
confidence: 99%